(3OjhGf ehSi Hf MSjf Hf ThGd GdYWajs - (3ehSi Hf MSjf Hf ThGd GdYWajs ((3eSYhO Hf CMeO Hf Ydi GdQeVGfi GdSehdi s)
(3ChdgG (B:s
(3GdMeO ddg GPi SHMJ dg GdSHY GdSehGJ CeG HYO agPG OjhGf GdTGYQ GdebhGd ehSi Hf MSjf Hf ThGd GdeYQha HEbdje YeGf jGeQHYkG CNfi Ydjg HdGDg HYO GdNdjW hWGd ajg KhGDg s
(3BNQgG (B:s
(3de jgOgG ZjdGfgG dHdGdg CHOkG (B[ (3h(B] (3de jSHb HgG CehjgG s
(3HgG fXGe GdJYbjHIs
(3eQJH GdbhGai Ydi MQha GdeYLes
(3YdjgG JedcGf CbOegeG SfI (B1256(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs